Penggunaan Media Kartu Putar dalam Penyuluhan Untuk Meningkatkan Pengetahuan Mencuci Tangan Memakai Sabun Pada Siswa SD Tegalrejo 2 Kota Yogyakarta - Ikfina Agustina; Siti Hani Istiqomah; Mohammad Mirza Fauzie (Poltekkes Kemenkes Yogyakarta, 2016)
The practice of handwashing with soap need to be applied in early age as a disease prevention effort. One of the important main target groups is elementary school students. Counseling can be maximally accepted if the media used is appropriate with the target. The appropriate media of elementary school students is something that attract their attention so that can enable the delivery of the messages, such as pictured media, and one of which is named “rotating cards”. This study was aimed to determine the effect of those cards used in a counselling for increasing the knowledge about handwashing with soap. The study was a quasi experiment with pre-test post-test control group design, and was condected in Tegalrejo 2 Elementary School of Yogya-karta City. The study subject consisted of 30 students of Grade IV A and V A as the treatment group and 30 students of class IV B and V B as the control group. The study results show that the use of “rotating cards” can increase the knowledge of treatment group (average=3,07) high-er than that of the control group (average=1,57). The statistical analysis using independent t-test obtained p value = 0,013, which shows that the difference is significant. Based on the re-sult, it can be concluded that the use of the card media in counseling activities, influences the knowledge of handwashing with soap among students of Tegalrejo 2 Elementary School.